Hyperbolic metamaterials based on quantum-dot plasmon-resonator nanocomposites - Zhukovsky, S. V. (2014)
We theoretically demonstrate that nanocomposites made of colloidal semiconductor quantum dot monolayers placed between metal nanoparticle monolayers can function as multilayer hyperbolic metamaterials. Depending on the thickness of the spacer between the quantum dot and nanoparticle layers, the effective permittivity tensor of the nanocomposite is shown to become indefinite, resulting in increased photonic density of states and strong enhancement of quantum dot luminescence. This explains the results of recent experiments [T. Ozel et al., ACS Nano 5, 1328 (2011)] and confirms that hyperbolic metamaterials are capable of increasing the radiative decay rate of emission centers inside them. The proposed theoretical framework can also be used to design quantum-dot/nanoplasmonic composites with optimized luminescence enhancement.